Choosing the optimal extraction method for European mistletoe - Trutaev, Sergey; Sayko, Irina; Sichkar, Antonina; Soldatov, Dmytro (Annals of Mechnikov’s Institute, 2023)
Introduction. The therapeutic properties of European Mistletoe (Viscum album L.) have been known since ancient times. This plant contains various biologically active compounds that contribute to its diverse pharmacological effects. Extracts from European Mistletoe have been found to exhibit direct cytotoxic and immunomodulating properties, making them suitable candidates for antitumor agents. The presence of polyphenolic and other compounds that dilate blood vessels, lower blood pressure, and reduce triglyceride levels in serum suggests that other extraction preparations from European Mistletoe could be recommended as standalone agents for the prevention and treatment of hypertension, angina, and vascular atherosclerosis. Objective. The study aimed to select a rational method for obtaining alcohol extract from European Mistletoe for the further development of a preparation with anti-atherosclerotic properties. The research had two main objectives: the selection of an effective extraction method and the determination of optimal extraction conditions for maximum recovery of the targeted BAC. Materials and Methods. Fresh shoots with leaves of European Mistletoe were selected as the subject of the study. After comminution and determination of key technological properties, extraction was carried out using the maceration method and extraction under variable pressure in the laboratory extractor "Timatic Micro 0.5" from the Italian company "Technolab". Results and Discussion. Comparative experimental studies were conducted to determine the optimal extraction method and main technological parameters for the extraction of the raw material. It was established that extracts obtained by the extraction method under variable pressure exhibited better quality indicators. The optimal extraction parameters for European Mistletoe shoots and leaves were determined as follows: fineness – 5±2 mm, "raw material: extract" ratio (DER) – 1:10, pressure – 5 atm, compression time – 3 min, decompression time – 3 min, number of cycles – 20, total process time – 120 min. Conclusions. Based on the conducted research, the extraction method under variable pressure was selected as the optimal approach for obtaining extracts from European Mistletoe. The effective extraction conditions were experimentally determined. Qualitative and quantitative evaluation of the obtained extract was conducted, confirming the correctness of choosing the extraction method for Viscum album. Keywords: European Mistletoe, cardiovascular diseases, extract, extraction under variable pressure, Timatic Micro extractor.